Methodological approaches and regulatory support for the control and assessment of the quality of construction works - Filippov, Oleksandr (Ways to Improve Construction Efficiency, 2022)
The article is devoted to the critical role of an effective system of control and assessment of the quality of construction works for the successful implementation of projects, especially in the context of current economic and security challenges in Ukraine. The analysis allows us to formulate a number of key conclusions regarding methodological approaches and regulatory support for this area.First, the fundamental requirement of comprehensiveness and multi-level control is emphasized. Quality assurance in construction is considered as a continuous process that covers the entire life cycle of the facility. Input, operational, acceptance, inspection and state control - each of them performs clearly defined functions, creating reliable, multi-layered protection against defects. Such a systematic approach, which meets the requirements of DSTU, allows you to promptly identify and eliminate problems at an early stage, which minimizes risks and costs for corrections.The emphasis is on the importance of planning and preventive measures. Quality control begins long before the actual construction, at the stage of design and formation of a detailed quality assurance program. This allows the integration of the necessary requirements and procedures at the conceptual stage, which is much more effective than reactive elimination of deficiencies.Digital transformation is defined as an indispensable condition for increasing the efficiency of quality management. Real-time data integration, automation of key business processes (especially inventory management, receivables and payables), as well as the use of advanced analytical tools and artificial intelligence allow construction companies to move from reactive to proactive quality and financial stability management. This digitalization ensures early detection of deviations, optimization of cash flows and a significant increase in the overall transparency and controllability of construction projects.It is emphasized that the successful implementation of the project directly depends on the effectiveness of the quality management system. The scheme of its organization, based on the cyclical principle of "plan-do-check-act" (PDCA), demonstrates that the detection and elimination of deviations should constantly lead to adjustment and optimization of the entire system. Such flexibility and adaptability are critically important for the construction industry in the context of economic instability and increased risks typical of Ukraine.